Pandemic patriotism: Official speeches in the face of the global COVID-19 crisis. (July 2022) - Atria, Jorge; Alfaro, Juan; Tapia, Magdalena; Frei, Raimundo
Faced with the COVID-19 pandemic, authorities have had to announce health, economic, financial, and social measures. The way in which these actors communicate is crucial and points to the collective meanings that are transmitted when dealing with the pandemic. The discourses used are designed with different frameworks and narratives to have broad appeal, so as to convince the public about the government's performance in managing the crisis and to obtain respect and obedience. Based on a qualitative analysis of 238 official speeches from five continents delivered between March and May 2020, this article contributes to the analysis of the pandemic with regard to two axes that underlie the speeches in other crises of this magnitude: appeals for solidarity and references to a war context. The results show that in this pandemic, the discourses have been deployed through these axes, reinforcing collective memories and national identities as sources to activate patriotic feelings and sustain implemented measures.